2011
DOI: 10.1080/01904167.2011.610489
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SOIL SATURATION ON DEVELOPMENT AND15N-NITRATE UPTAKE EFFICIENCY OF TWO WARM SEASON GRASSES EMERGING FROM DORMANCY

Abstract: 2 Use of effluent on turfgrass is increasing due to population growth and limited water supplies. Because effluent is generated continuously, turf managers may be forced to over-irrigate, leading to soil saturation. Although the nutrients in effluent are readily absorbed by turf, the effects of prolonged soil saturation on uptake are unknown. This research examined the impact of soil saturation on plant development and nitrate uptake of two warm-season turfgrasses emerging from dormancy. Dormant grass/soil cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The 15 N recovery from plant, soil, and leachate in our experiment were higher than Wherley et al. (2011), lower than Fagerness et al. (2004), and similar to Miltner et al.…”
Section: Discussionsupporting
confidence: 87%
“…The 15 N recovery from plant, soil, and leachate in our experiment were higher than Wherley et al. (2011), lower than Fagerness et al. (2004), and similar to Miltner et al.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies demonstrated that bermudagrass plants are quite tolerant of submersion, even for an extended period. Wherley et al (2011) studied the response to soil saturation over 72 days on plant development of two warm-season species: common centipedegrass [Eremochloa ophiuroides (Munro) Hack] and 'Tifway 419' hybrid bermudagrass [Cynodon dactylon (L.) Pers. × C. transvalensis Burtt Davy].…”
Section: Summary Bermudagrass (Cynodon Spp) At the Mature Stage Is Qmentioning
confidence: 99%